Co-culturing of Fungal Strains Against Botrytis cinerea as a Model for the Induction of Chemical Diversity and Therapeutic Agents - Serrano, Rachel; González-Menéndez, Víctor; Rodríguez, Lorena; Martín, Jesús; Tormo, José R.; Genilloud, Olga (Frontiers in Microbiology, 2017)
New fungal secondary metabolites (SMs) have been successfully described to be produced by means of in vitro-simulated microbial community interactions. Co-culturing of fungi has proved to be an efficient way to induce cell-cell interactions that can promote the activation of cryptic pathways, frequently silent when the strains are grown in laboratory conditions. Filamentous fungi represent one of the most diverse microbial groups known to produce bioactive natural products. Triggering the production of novel antifungal compounds in fungi could respond to the current needs to fight health compromising pathogens and provide new therapeutic solutions. In this study, we have selected the fungus Botrytis cinerea as a model to establish microbial interactions with a large set of fungal strains related to ecosystems where they can coexist with this phytopathogen, and to generate a collection of extracts, obtained from their antagonic microbial interactions and potentially containing new bioactive compounds. The antifungal specificity of the extracts containing compounds induced after B. cinerea interaction was determined against two human fungal pathogens (Candida albicans and Aspergillus fumigatus) and three phytopathogens (Colletotrichum acutatum, Fusarium proliferatum and Magnaporthe grisea). In addition, their cytotoxicity was also evaluated against the human hepatocellular carcinoma cell line (HepG2). We have identified by LC-MS the production of a wide variety of known